Seasonal and year‐to‐year variation of mercury concentration in perch (Perca fluviatilis) in boreal lakes. (22nd September 2014) - Braaten, Hans Fredrik Veiteberg; Fjeld, Eirik; Rognerud, Sigurd; Lund, Espen; Larssen, Thorjørn
Abstract The authors examined the seasonal and year‐to‐year variations of mercury (Hg) concentrations in populations of perch (Perca fluviatilis) from 2 boreal freshwater lakes in southeast Norway. Fish Hg concentrations were determined seasonally (spring, summer, and autumn) over 3 yr (2010, 2011, and 2012) to test the hypothesis that there are substantial changes in fish Hg concentrations during the year (seasonal variation) as well as annually. Concentrations were significantly (p < 0.0001) different in the 2 study lakes, with mean seasonal concentrations varying from 0.24 mg/kg to 0.36 mg/kg and from 0.29 mg/kg to 0.37 mg/kg, respectively. The Hg concentrations of both perch populations showed significant year‐to‐year (p < 0.0001) and seasonal variation (p < 0.01). The changing fish Hg concentrations were 25% and 28% (2010–2011) and 17% and 0% (2011–2012) in the 2 lakes over the 3 yr, respectively. The results demonstrate how the significant year‐to‐year increase is, among other variables, related to changes in trophic position, shown through stable nitrogen (δ15N) isotope data. The seasonal variation is related to summer growth dilution. The results highlight the clear need for yearly studies of fish Hg concentrations, rather than the 3‐yr cycle suggested by current European policy through the Water Framework Directive. The lack of yearly sampling may result in erroneous conclusions regarding fish Hg concentration time trends. Environ Toxicol Chem 2014;33:2661–2670. © 2014 SETAC